Financial and economic determinants of banks financial distress in MENA region - Abdelmoneim Metwally; Mai M. Yasser; Eman Adel Ahmed; Mohamed Ali Shabeeb Ali (Economies, 2025)
This study investigates the influences of financial performance and economic determinants (inflation rate and economic growth) on financial distress (FD) in the MENA region in the context of the contagion effect theory and Minsky's financial instability theory. This paper examines the determinants of financial distress in the MENA region from 2002 until 2020 using pooled OLS, fixed effect, and GMM panel estimation models; then the results are used to estimate the effect over the long run. The results show that the things that cause financial distress are changing a lot between countries in the MENA region. This shows how important it is to separate the effects of economic and financial factors. The results show the significance of economic growth, ROA, ROE, inflation, and stock market profitability using fixed effects. The results changed when we used GMM, concluding that economic growth, ROA, ROE, and stock market profitability were significant, while inflation was not significant. Therefore, there is a significant and negative relationship between financial distress and economic growth in GCC-MENA as well as other MENA countries. Our results can be of importance to investors and regulators. The introduction of a more stable political environment and engagement in international economic and financial markets will decrease the negative impacts of financial distress and boost economic growth and its sustainability in the MENA region.
Keywords: D53; E31; G32; O42; 330; financial distress; economic growth; MENA; ROA; GCC; inflation; banking sector